Downregulation of Dickkopf-1 is responsible for high proliferation of breast cancer cells via losing control of Wnt/β-catenin signaling - Zhou Xiao-lei; Qin Xiao-ran; Zhang Xiao-dong; Ye Li-hong (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the role of DKK-1/Wnt/β-catenin signaling in high proliferation of LM-MCF-7 breast cancer cells, a sub-clone of MCF-7 cell line. Methods: Two cell lines (MCF-7 and LM-MCF-7) with different proliferation abilities were used. LM-MCF-7 cells were transiently transfected with the pcDNA3-DKK-1 plasmid encoding the DKK-1 gene (or MCF-7 cells were transfected siRNA targeting DKK-1 mRNA). Flow cytometry analysis and 5-bromo-2′-deoxyuridine (BrdU) incorporation assay were applied to detect the cell proliferation. The expression levels of β-catenin, phosphorylated β-catenin, c-Myc, cyclin D1 and Survivin were examined by Western blot analysis. The regulation of Survivin was investigated by Luciferase reporter gene assay. Results: Western blot and RT-PCR analysis showed that the expression level of DKK-1 was downregulated in LM-MCF-7 relative to MCF-7 cells. Flow cytometry and BrdU incorporation assay showed DKK-1 could suppress growth of breast cancer cells. Overexpression of DKK-1 was able to accelerate phosphorylation-dependent degradation of β-catenin and downregulate the expression of β-catenin, c-Myc, cyclin D1 and Survivin. Luciferase reporter gene assay demonstrated that Survivin could be regulated by β-catenin/TCF4 pathway. Conclusion: We conclude that the downregulation of DKK-1 is responsible for the high proliferation ability of LM-MCF-7 breast cancer cells via losing control of Wnt/β-catenin signaling pathway, in which c-Myc, cyclinD1 and Survivin serve as essential downstream effectors. Our finding provides a new insight into the mechanism of breast cancer cell proliferation.